Next level virtual training : advance your facilitation - Howles, Diana L. (ATD Press, 2022)
As virtual training continues as a go-to, effective learning option, and platform providers improve functionality, trainers and facilitators need to take their skills to the next level. Written by expert facilitator Diana L. Howles, this book goes beyond the basics of virtual training and online synchronous instruction, providing in-depth insights into advanced challenges. Next Level Virtual Training introduces the Virtual Trainer Capability Model, which identifies eight areas of expertise for the top virtual professional. A train-the-virtual-trainer resource, this book will guide you in developing the specific knowledge and skills to facilitate online interactivity, manage multitasking, be technically fluent, oversee logistics and troubleshooting, leverage your voice, and engage virtual learners. Importantly, this book is about actionable tips, strategies, and techniques rather than the technologies. Inside you’ll find comprehensive chapters on developing on-camera competence; applying learning experience design to live online learning; and preparing for the combination of onsite and online learners together in a post-pandemic hybrid work environment. Whether you are a virtual trainer, a live online facilitator, a synchronous educator, an online adult education instructor, this book is for you. It is also for designers, developers, evaluators, and producers of virtual learning.